Institutional obstacles and opportunities for policy entrepreneurship in cross-border environmental management: a case study in China's Greater Pearl River Delta region. Issue 2 (3rd July 2019) - Chu, Vivian H. Y.; Lee, Anna Ka-yin
ABSTRACT: Air pollution was placed very low on China's policy agenda in the 1990s. Sharing the PRD's Southern border, Hong Kong became increasingly concerned with the pollution originating from their rapidly developing neighbors. This paper offers an explanatory study for the implementation of a trans-boundary air quality monitoring network in 2005 which was, in many ways, considered a breakthrough in environmental cooperation in this region. Empirical evidence demonstrates that extended efforts from a Hong Kong official had eventually triggered the Guangdong provincial government and the Hong Kong government to undertake a range of collaborative measures to improve regional air quality, including the establishment of the Pearl River Delta regional air quality monitoring network in 2005. Building upon the concept of "policy entrepreneurship, " this study discovers that the policy entrepreneur's political rank endowed him with direct access to the formal cross-border institution, through which he was able to build a close professional relationship with his mainland counterparts and enables him to be a transfer agent. This case illustrates that state actors are well-placed in this region's trans-boundary platforms to initiate the transfer of policy innovations to neighboring governments, which prompts the formulation of cooperative projects. Nonetheless, this paper also cautions that effective cross-border collaboration is still largely dependent upon the contextual framework of the authoritarian governance regime whereby the interactions between policymakers and implementers are fundamentally shaped by institutional design and incentives.